The Protein Kinase SmSnRK2.6 Positively Regulates Phenolic Acid Biosynthesis in Salvia miltiorrhiza by Interacting with SmAREB1 - Jia, Yanyan; Bai, Zhenqing; Pei, Tianlin; Ding, Kai; Liang, Zongsuo; Gong, Yuehua (Frontiers in Plant Science, 2017)
Subclass III members of the sucrose non-fermenting-1-related protein kinase 2 (SnRK2) play essential roles in both the ABA signaling and abiotic stress responses of plants by phosphorylating the downstream ABA-responsive element (ABRE)-binding proteins (AREB/ABFs). This comprehensive study investigated the function of new candidate genes, namely SmSnRK2.3, SmSnRK2.6, and SmAREB1, with a view to breeding novel varieties of Salvia miltiorrhiza with improved stress tolerance stresses and more content of bioactive ingredients. Exogenous abscisic acid strongly induced the expression of these genes. PlantCARE predicted several hormones and stress response cis-elements in their promoters. SmSnRK2.6 and SmAREB1 showed the highest expression levels in the leaves of S. miltiorrhiza seedlings, while SmSnRK2.3 exhibited a steady expression in their roots, stems, and leaves. A subcellular localization assay revealed that both SmSnRK2.3 and SmSnRK2.6 were located in the cell membrane, cytoplasm, and nucleus, whereas SmAREB1 was exclusive to the nucleus. Overexpressing SmSnRK2.3 did not significantly promote the accumulation of rosmarinic acid (RA) and salvianolic acid B (Sal B) in the transgenic S. miltiorrhiza hairy roots. However, overexpressing SmSnRK2.6 and SmAREB1 increased the contents of RA and Sal B, and regulated the expression levels of structural genes participating in the phenolic acid-branched and side-branched pathways, including SmPAL1, SmC4H, Sm4CL1, SmTAT, SmHPPR, SmRAS, SmCHS, SmCCR, SmCOMT, and SmHPPD. Furthermore, SmSnRK2.3 and SmSnRK2.6 interacted physically with SmAREB1. In summary, our results indicate that SmSnRK2.6 is involved in stress responses and can regulate structural gene transcripts to promote greater metabolic flux to the phenolic acid-branched pathway, via its interaction with SmAREB1, a transcription factor. In this way, SmSnRK2.6 contributes to the positive regulation of phenolic acids in S. miltiorrhiza hairy roots.